Prospects for a multipolar international monetary system - Mansoor Dailami; Paul Masson (Danish Institute for International Studies (DIIS), 2011)
In this DIIS Report, Dr Mansoor Dailami and Professor Paul Masson envisage a fundamental change in the international monetary system, one that is likely to recognize the growing economic and financial clout of emerging market economies, particularly China. The authors see three possible international currency scenarios for the period 2011-25 emerging. First, the US dollar's dominance remains unchallenged. Second, a multipolar international monetary system emerges, most likely with the dollar, euro, and renminbi at the center. Third, dissatisfaction with an international currency system based on national currencies leads to reforms that make supply of the world's currency the result of multilateral decisions.
Keywords: 300